Analyzing and Understanding the Salient Features Right to Development: Analyzing the Declaration on Right to Development (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The “Right to Development” is an inalienable human right by virtue of which everyone is entitled to participate in, contribute to and enjoy economic, social, cultural, and political development, in which all human rights and fundamental freedoms can be fully realised”, it undoubtedly includes rights to accomplishment of basic needs as one of the inherent facet of the right to development, an indispensable component of the enjoyment of economic and social development. However, in several ways the right to development goes further than what the majority would define as realization of basic needs. In many sense it extends to cultural and political development, which is usually not included in the basic needs approach. The Right to Development additionally entails lively accomplishments, i.e., to raise living standards with the passage of time, whereas the basic needs approach is principally concerned with granting certain standards to each one at earliest point of time, and less concerned with growth over time. Moreover, economic development is an attribute of a society as a whole, while basic needs fulfillment and rights concern rights of individuals within society. These distinctions can be over- drawn, since a dynamic version of basic needs must include, as one can see, improving standards over time, while there is interdependence between individuals' fulfillment of basic needs and what is happening to society as a whole. Through this article researcher intends to examine the contents and nature of “Declaration on Right to development, 1986” by the United Nations.